Combined biology-guided radiotherapy and Lutetium PSMA theranostics treatment in metastatic castrate-resistant prostate cancer - Gaudreault, Mathieu; Chang, David; Hardcastle, Nicholas; Jackson, Price; Kron, Tomas; Hofman, Michael S.; Siva, Shankar (Frontiers in Oncology, 2023)
Background Lutetium-177 [177Lu]-PSMA-617 is a targeted radioligand that binds to prostate-specific membrane antigen (PSMA) and delivers radiation to metastatic prostate cancer. The presence of PSMA-negative/FDG-positive metastases can preclude patients from being eligible for this treatment. Biology-guided radiotherapy (BgRT) is a treatment modality that utilises tumour PET emissions to guide external beam radiotherapy. The feasibility of combining BgRT and Lutetium-177 [177Lu]-PSMA-617 for patients with PSMA-negative/FDG-positive metastatic prostate cancer was explored. Material and methods All patients excluded from the LuPSMA clinical trial (BLINDED FOR REVIEW) due to PSMA/FDG discordance were retrospectively reviewed. A hypothetical workflow where PSMA-negative/FDG-positive metastases would be treated with BgRT whilst PSMA-positive metastases would be treated with Lutetium-177 [177Lu]-PSMA-617 was considered. Gross tumour volume (GTV) of PSMA-negative/FDG-positive tumours were delineated on the CT-component of the FDG PET/CT scan. Tumours were deemed suitable for BgRT if (1) normalised SUV (nSUV), defined as the ratio of maximum SUV (SUVmax) inside the GTV to mean SUV inside a 5mm/10mm/20mm margin expansion of the GTV, was larger than a pre-specified nSUV threshold and (2) there was no PET avidity inside the margin expansion. Results In 75 patients screened for Lutetium-177 [177Lu]-PSMA-617 treatment, 6 patients were excluded due to PSMA/FDG discordance and 89 PSMA-negative/FDG-positive targets were identified. GTV volumes ranged from 0.3 cm3 to 186 cm3 (median GTV volume = 4.3 cm3, IQR = 2.2 cm3 – 7.4 cm3). SUVmax inside GTVs ranged between 3 and 12 (median SUVmax = 4.8, IQR = 3.9 – 6.2). With nSUV ≥ 3, 67%/54%/39% of all GTVs were suitable for BgRT within 5mm/10mm/20mm from the tumour. Bone and lung metastases were the best candidates for BgRT (40%/27% of all tumours suitable for BgRT with nSUV ≥ 3 within 5 mm from the GTV were bone/lung GTVs). Conclusions: Combined BgRT/Lutetium-177 [177Lu]-PSMA-617 therapy is feasible for patients with PSMA/FDG discordant metastases.